A new species of branchial fish parasitic isopod, Norileca Bruce, 1990 (Crustacea: Isopoda: Cymothoidae), from the Andaman Islands, India. Issue 7 (14th September 2021) - Nashad, Musaliyarakam; Aneesh, Panakkool Thamban; Kumar, Appukuttannair Biju; Bineesh, Kinattumkara
ABSTRACT: Norileca hathai Aneesh, Nashad and Kumar sp. nov., parasitizing the blacktip trevally, Caranx heberi (Bennett, 1830) (Carangidae) from off Burmanallah, South Andaman, India is described and illustrated. Norileca hathai sp. nov., the fourth species of Norileca Bruce, 1990, is characterized by: body twisted to one side; small body size (10–12 mm); dark stripes on pereonites 5–7, pleonites 1–5 and pleotelson, except the medial and posterio-lateral margins; coxae 3–7, 0.5 times as long as pereonites; presence of robust setae on the propodus of pereopods 1–3; pleotelson round and 0.85 as long as wide; uropod 0.85 as long as pleotelson; maxilla both lobes with 2 robust setae. A table of the inter-specific characters between the species of Norileca Bruce, 1990 and a revised key to the species are provided.